Narsisme CEO dan CSR - Putranto, Yohanes Andri (Catholic University Musi Charitas, 2022)
This study has the aim of empirically testing whether CEO narcissism has a correlation with CSR activities. Upper Echelon Theory is used to explain CEO narcissism can correlate with CSR activity. Measurement of CEO narcissism focuses on the company's annual report which in this case the development of previous research instruments. The CSR variable in this study was measured using the Sri Kehati index. In this case, companies that enter the Sri Kehati index are companies whose CSR performance is good. The research sample was IDX issuers who entered the LQ45 index in the period 2017 - 2019. Hypothesis testing using the Chi Square correlation test with PSPP applications. The results of hypothesis testing concluded that CEO narcissism correlated with CSR policy.